CLINICAL FEATURES, DIAGNOSIS AND TREATMENT OUTCOMES OF WOMEN WITH FIBROADENOMA OF THE MAMMARY GLANDS - Azizova, G.D.; Lutpillaeva , A.M.; Tuxtabaeva , M.T. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The study included 201 women aged 18-45 years who visited the outpatient clinic of the Tashkent regional branch of the Republican Scientific and Practical Center of Oncology and Radiology in 2024. The results showed that the largest number of patients (61.5%) were aged 18 to 35 years. Ultrasound examination was used for diagnosis in all patients, mammography in 24%. According to the results of ultrasound diagnostics, 65 cases (32.5%) had fibroadenomas of less than 10 mm in size in 37 cases (18.5%) and 25 cases (12.5%) of 20 to 30 mm in size. Surgical treatment in the form of fibroadenoma excision was performed in 31 patients (15.5%), 32.2% of whom had a tumor relapse within 1.5-2 years. Postoperative complications were observed in 9.6% of patients. Thus, every third operated patient had a recurrent fibroadenoma, which emphasizes the need for a comprehensive and individual approach to the treatment of this pathology.